USB storage authentication, delegation and revocation mechanisms based on multilevel trust model [electronic resource] - Mahboubi, Arash, 1981- (2013)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2013